The Use of Social Media as A Means of Marketing by MSMEs In the Era of Digitalization - Nisrina Afifah Dwitani; Eko Putro Widoyoko (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
In the midst of economic uncertainty and the transition from non-renewable natural resources, Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy. Even though technological developments continue, many MSMEs have not yet utilized it, especially social media as a marketing tool to improve their business performance in the digital era. This research aims to describe the use of social media as a marketing tool for MSMEs in the era of digitalization. The method used is library research, with a focus on the role of social media as a marketing tool for MSMEs. This research discusses the extent to which social media is used as a marketing tool for MSMEs in the digital era to increase sales, as well as the advantages and disadvantages of using social media as a marketing tool. Literature analysis was carried out by collecting data from relevant scientific articles published on Google Scholar between 2019 and 2024. The research results show that the use of social media by MSMEs provides many benefits, including building a stronger brand image and increasing customer loyalty. However, despite much progress, MSMEs still face various challenges in the era of digitalization.